Growth and eficiency of sall scale industry and its impact on economic development of Sindh - Mumtaz Ali Junejo; Muhammad Nawaz Chand (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2008)
The purpose of this study is to analyze the growth, efficiency, causes of sickness of small scale industry, emergence of entrepreneur and competencies of entrepreneurs at Larkana estate area of Sindh Province. The study examines the educational background of the entrepreneurs of small scale industry who are the helm of affairs and its impact on the growth of sales of the every year. Strong evidence emerges that owners of small industrial units are family concern and having a low educational background, lack of managerial knowledge and conservation-oriented attitude results in under utilization of capacity and low growth of units established every year. This research paper provides a survey of the theoretical and empirical literature relating to promote the small scale industry in the Larkana region. This study indicates effective policy measures to promote the small scale industry particularly in Larkana region and generally in Pakistan.
Keywords: 330; Small scale industry; Skilled entrepreneurs; Sindh; Larkana